(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2024)
A novel, rapid, accurate, precise and simple stability indicating RP-HPLC method has been proposed and validated for the concurrent quantitation of Dapagliflozin and Metoprolol succinate in laboratory prepared mixture. The greenness assessment of the proposed approach was accomplished utilizing GAPI and AGREE tools. The final chromatographic run was performed utilizing Methanol: 20mM Potassium Dihydrogen Phosphate: (70:30) as eluent, injected at 25°C at a rate of 1.5 mL/min. Cosmosil-MS-5 C18 column (250 mm × 4.6 mm, 5 μm) was utilised and estimation was done using 223 nm. The APIs were exposed to stress environments (oxidation, acidic and basic hydrolysis, photolysis and thermal stimuli) and stressed samples were analysed under same chromatographic condition. Dapagliflozin and metoprolol succinate had retention times of 11.6 and 2.6 minutes, correspondingly. It was demonstrated having linearity within 10-30 µg/mL for Dapagliflozin and 50–150 µg/mL for Metoprolol succinate. The % accuracy for Dapagliflozin were in the range of 99.01 - 100.56 %, while for Metoprolol succinate it was within 99.32 - 101.41 % at three levels. The outcomes for precision study were within the limits. For Dapagliflozin, the LOD and LOQ were 0.49 µg/mL and 0.59 µg/mL correspondingly and for Metoprolol succinate, values were 1.48 µg/mL and 1.79 µg/mL correspondingly. The approach is effectively suggested for stability-indicating research as well as for routine estimation of Dapagliflozin and Metoprolol succinate in bulk and laboratory prepared mixture. Furthermore, AGREE and GAPI outcomes confirmed the developed approach’s eco–friendliness and greenness.